KOMODIFIKASI UPACARA NGABEN DI DESA LEGIAN KUTA BADUNG - Sukrayasa, I Wayan; D.E., Relin; Wiguna, I Made Arsa (Pangkaja: Jurnal Agama Hindu, 2025)
This research aims to examine the phenomenon of commodification of the Ngaben ceremony in Legian Village, Kuta, Badung, Bali. Ngaben, which is an important ritual in Hinduism in Bali, is experiencing significant changes along with increasing tourism and commercialization in the region. This research uses a qualitative approach with descriptive methods to gain an in-depth understanding of the process and impact of the commodification of the Ngaben ceremony. Data was collected through in-depth interviews with key informants, participant observation and documentation. Key informants include traditional leaders, ceremony holders, and business actors involved in the commodification process. The research results show that the commodification of the Ngaben ceremony not only has an impact on economic aspects, but also brings changes to the cultural and social values of the local community. The once sacred Ngaben ceremony is now often adapted to attract tourists, leading to a shift in the meaning and purpose of the ceremony. These findings indicate that although commodification provides economic benefits for society, there are concerns regarding the preservation of the traditional and spiritual values of the Ngaben ceremony. This research recommends the need for a balanced policy between tourism development and cultural preservation so that the essence of the Ngaben ceremony is maintained.